2020
DOI: 10.18280/ijht.380417
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Energy Efficiency Design of Building Facade and Its Thermodynamic Evaluation

Abstract: Needless to say, green buildings have now become an inevitable trend for the sustainable development of society, and they have paved a way for the harmonious coexistence between man and nature. The design of building facade is an important part in green building construction, to achieve the optimal energy-saving effect of building facade, scholars in the field have attached great importance to this aspect and they have done works to optimize it from constituent materials, structural forms, and thermal insulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…The thickness of insulation material determined by calculating the annual operating cost containing annual depreciation and energy loss is called the "economical thickness", and it is the minimum value of annual operating cost. In terms of the economical thickness of exterior wall insulation layer, world field scholars drew on the theory of life cycle evaluation to build economics models of insulation layer thickness for different types of buildings under different climatic conditions, they conducted research from different design angels and proposed methods for determining the economical thickness of insulation layer [14][15][16][17][18][19][20][21][22][23][24][25], and it's found that the regional climate features, building type, operating mode, and the differences in economic and technical levels can all affect the requirements of thermal insulation and energy conservation [26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Relationship Between Insulation Layer Thickness Of Exterior ...mentioning
confidence: 99%
“…The thickness of insulation material determined by calculating the annual operating cost containing annual depreciation and energy loss is called the "economical thickness", and it is the minimum value of annual operating cost. In terms of the economical thickness of exterior wall insulation layer, world field scholars drew on the theory of life cycle evaluation to build economics models of insulation layer thickness for different types of buildings under different climatic conditions, they conducted research from different design angels and proposed methods for determining the economical thickness of insulation layer [14][15][16][17][18][19][20][21][22][23][24][25], and it's found that the regional climate features, building type, operating mode, and the differences in economic and technical levels can all affect the requirements of thermal insulation and energy conservation [26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Relationship Between Insulation Layer Thickness Of Exterior ...mentioning
confidence: 99%